Accounting disclosure in financial statements and its impact on current and prospective investors decisions (Czech Journal of Multidisciplinary Innovations, 2024)
The aim of this article is to clarify the relationship between the quality of accounting information contained in the financial statements published by joint-stock companies and financial institutions operating in the Iraqi Stock Exchange, considering those lists an essential tool for accounting disclosure, and the audience of users of those financial statements, including current and prospective investors, and how to improve the quality of that accounting information. What are the financial statements and their usefulness for their users and what are the characteristics or qualities of the accounting information and the annexed and supplementary explanations and disclosures and the relationship between them and investors in terms of the timeliness of their presentation and dissemination The article also indicates the position of shareholders in the Iraqi market and demands the dissemination of more detailed information about those companies' economic activities and the relevance of financial statement to disclose the information to be available and the ways in which it is prepared in accordance with international accounting standards.